Social and geographical distribution of mobility-related greenhouse gas emissions in Poznań and Tri-city functional urban areas - Czepkiewicz, Michał; Brudka, Cezary; Krysiński, Dawid; Schmidt, Filip (Quaestiones Geographicae, 2024)
Mobility is an important source of greenhouse gas (GHG) emissions and a major contributor to human-induced climate change. Much of these emissions result from urban residents’ travel within urban areas (i.e. short-distance travel [SDT]) and away from them (i.e. long-distance travel [LDT]). In this study, we focus on the distribution of mobility-related GHG emissions in two functional urban areas in Poland: Poznań and the Tri-city. Using data from a representative survey (N 2000 in each area), we investigate the emission distribution and associations between emission levels and the socio-economic characteristics and residential locations of study participants. Emission levels are unequally distributed: the top 10% of emitters contribute >50% of SDT and LDT emissions. People with high education and income levels tend to travel and emit more within and away from the cities. People of retirement age travel and emit much less than the younger people. SDT emission levels are clustered spatially and increase with the increasing distance from the main city centres and decreasing density. LDT emissions have only very weak or no association with residential location.